DEPRESSION-RELATED FACTORS IN PULMONARY TUBERCULOSIS PATIENTS: SECONDARY ANALYSIS OF THE INDONESIAN HEALTH SURVEY 2023: Faktor Terkait Depresi pada Kasus Tuberkulosis Paru: Analisis Sekunder Survei Kesehatan Indonesia 2023 - Regina, Agave; Nasution, Helmi Suryani; Syukri, Muhammad; Halim, Rd.; Putra, Ashar Nuzulul; Pratiwi, Dessy; Yuliana, Roma (Universitas Airlangga, 2026)
Background: Depression is highly prevalent among tuberculosis (TB) patients, with reported rates reaching 31-61%, and it is strongly associated with poor medication adherence and adverse treatment outcomes. Despite this considerable burden, mental health screening for TB patients has not yet been integrated into routine TB care. Purpose: This study aimed to identify factors associated with depression among TB patients. Methods: This secondary data analysis used the Survei Kesehatan Indonesia (SKI) or Indonesian Health Survey 2023 with a cross-sectional design. A total sampling approach was applied, to all TB patients who met the inclusion criteria, resulting in 1,163 respondents. Statistical analyses included the chi-square test and multiple logistic regression, with a significance level of p < 0.05. Results: The prevalence of depression among TB patients was 5.38% (95% CI: 3.26–8.76%). Multivariate analysis showed that being female [aPOR = 15.90, 95% CI (1.99-143.09)], age 15-40 years [aPOR = 5.80, 95% CI (1.17-28.67)], TB treatment duration ≤6 months [aPOR = 5.22, 95% CI (1.67-16.34)], smoking [aPOR = 11.33, 95% CI (2.07-61.97)], and stress [aPOR = 39.04, 95% CI (11.23-135.66)] were significantly associated with depression in TB patients. Stress was identified as the most influential factor. Conclusion: Depression remains a relevant issue among TB patients in Indonesia, with stress emerging as the strongest associated factor. Routine depression screening and integrated mental health support within TB programs are strongly warranted, particularly for high-risk groups such as women, younger adults, patients in the early phase of treatment, smokers, and those experiencing stress.